Falling back on forests: how forest-dwelling people cope with catastrophe in a changing landscape - Liswanti, N.; Sheil, Douglas; Basuki, I.; Padmanaba, M.; Mulcahy, G. (2011)
How do tropical forest people cope with natural disasters? We worked with four communities in East Kalimantan (Borneo), Indonesia, before and after a catastrophic flood. We interviewed 42 of 102 heads of households affected by the floods. All 42 households suffered some major loss of property – crops, lands, houses, and/or livestock. Each household adopted one or more coping strategies: increasing their reliance on forest resources; seeking paid employment; relocating their houses; and finding temporary land to establish their crops in upland areas. Immediate reliance on the forest was greatest for those most heavily impacted, the poorest, the least well educated, and those with the easiest access. Overall, those with the fewest resources and alternatives made most use of the forest. But access to such forest benefits is becoming increasingly difficult. The often crucial value of forests to local forest-dwellers needs to be better recognized in the context of current developments. These forest derived safety-values should be maintained or – where necessary – substituted.